Calcium supplementation for prevention of primary hypertension - Cormick, Gabriela (2021)
Background: Hypertension is a major public health problem that increases the risk of cardiovascular and kidney diseases. Several studies have shown an inverse association between calcium intake and blood pressure, as small reductions in blood pressure have been shown to produce rapid reductions in vascular disease risk even in individuals with normal blood pressure ranges. This is the first update of the review to evaluate the effect of calcium supplementation in normotensive individuals as a preventive health measure. Objectives: To assess the efficacy and safety of calcium supplementation versus placebo or control for reducing blood pressure in normotensive people and for the prevention of primary hypertension. Search methods: The Cochrane Hypertension Information Specialist searched the following databases for randomised controlled trials up to September 2020: the Cochrane Hypertension Specialised Register, CENTRAL (2020, Issue 9), Ovid MEDLINE, Ovid Embase, the WHO International Clinical Trials Registry Platform, and the US National Institutes of Health Ongoing Trials Register, ClinicalTrials.gov. We also contacted authors of relevant papers regarding further published and unpublished work. The searches had no language restrictions. Selection criteria: We selected trials that randomised normotensive people to dietary calcium interventions such as supplementation or food fortification versus placebo or control. We excluded quasi-random designs. The primary outcomes were hypertension (defined as blood pressure ≥ 140/90 mmHg) and blood pressure measures. Data collection and analysis: Two review authors independently selected trials for inclusion, abstracted the data and assessed the risks of bias. We used the GRADE approach to assess the certainty of evidence. Main results: The 2020 updated search identified four new trials. We included a total of 20 trials with 3512 participants, however we only included 18 for the meta-analysis with 3140 participants. None of the studies reported hypertension as a dichotomous outcome. The effect on systolic and diastolic blood pressure was: mean difference (MD) -1.37 mmHg, 95% confidence interval (CI) -2.08, -0.66; 3140 participants; 18 studies; I2 = 0%, high-certainty evidence; and MD -1.45, 95% CI -2.23, -0.67; 3039 participants; 17 studies; I2 = 45%, high-certainty evidence, respectively. The effect on systolic and diastolic blood pressure for those younger than 35 years was: MD -1.86, 95% CI -3.45, -0.27; 452 participants; eight studies; I2 = 19%, moderate-certainty evidence; MD -2.50, 95% CI -4.22, -0.79; 351 participants; seven studies; I2 = 54%, moderate-certainty evidence, respectively. The effect on systolic and diastolic blood pressure for those 35 years or older was: MD -0.97, 95% CI -1.83, -0.10; 2688 participants; 10 studies; I2 = 0%, high-certainty evidence; MD -0.59, 95% CI -1.13, -0.06; 2688 participants; 10 studies; I2 = 0%, high-certainty evidence, respectively. The effect on systolic and diastolic blood pressure for women was: MD -1.25, 95% CI -2.53, 0.03; 1915 participants; eight studies; I2 = 0%, high-certainty evidence; MD -1.04, 95% CI -1.86, -0.22; 1915 participants; eight studies; I2 = 4%, high-certainty evidence, respectively. The effect on systolic and diastolic blood pressure for men was MD -2.14, 95% CI -3.71, -0.59; 507 participants; five studies; I2 = 8%, moderate-certainty evidence; MD -1.99, 95% CI -3.25, -0.74; 507 participants; five studies; I2 = 41%, moderate-certainty evidence, respectively. The effect was consistent in both genders regardless of baseline calcium intake. The effect on systolic blood pressure was: MD -0.02, 95% CI -2.23, 2.20; 302 participants; 3 studies; I2 = 0%, moderate-certainty evidence with doses less than 1000 mg; MD -1.05, 95% CI -1.91, -0.19; 2488 participants; 9 studies; I2 = 0%, high-certainty evidence with doses 1000 to 1500 mg; and MD -2.79, 95% CI -4.71, 0.86; 350 participants; 7 studies = 8; I2 = 0%, moderate-certainty evidence with doses more than 1500 mg. The effect on diastolic blood pressure was: MD -0.41, 95% CI -2.07, 1.25; 201 participants; 2 studies; I2 = 0, moderate-certainty evidence; MD -2.03, 95% CI -3.44, -0.62; 1017 participants; 8 studies; and MD -1.35, 95% CI -2.75, -0.05; 1821 participants; 8 studies; I2 = 51%, high-certainty evidence, respectively. None of the studies reported adverse events. Authors' conclusions: An increase in calcium intake slightly reduces both systolic and diastolic blood pressure in normotensive people, particularly in young people, suggesting a role in the prevention of hypertension. The effect across multiple prespecified subgroups and a possible dose response effect reinforce this conclusion. Even small reductions in blood pressure could have important health implications for reducing vascular disease. A 2 mmHg lower systolic blood pressure is predicted to produce about 10% lower stroke mortality and about 7% lower mortality from ischaemic heart disease. There is a great need for adequately-powered clinical trials randomising young people. Subgroup analysis should involve basal calcium intake, age, sex, basal blood pressure, and body mass index. We also require assessment of side effects, optimal doses and the best strategy to improve calcium intake.